EVALUATION OF THE IMPACT OF OIL PRESENCE IN THE AVIATION FUEL ON PARTICLE SIZE DISTRIBUTION - Remigiusz JASIŃSKI; Jacek PIELECHA (Scientific Journal of Silesian University of Technology. Series Transport, 2017)
Emissions from aircraft engines represent a highly complex and important issue, which is related to the risk to human health. Particles emitted in urban areas and in the vicinity of airports affect air quality and have a particularly negative impact on airport workers. The development of measurement techniques and the methodology for evaluating exhaust emissions have allowed for the elaboration of appropriate procedures for the certification of aircraft and the enhancement of existing standards. Particulate matter emissions depend, among other things, on the composition of the fuel used and its additives. Some aircraft engine designs require a fuel additive in the form of oil, which ensures the proper operation of the fuel supply system. This article presents the results of studies conducted on jet engines powered by clean aviation fuel and fuel with the addition of oil. The aim of the study was to evaluate the effect of the addition of oil on the size distribution and concentration of emitted particles. It was found that, for small values of thrust, oil additive increases the concentration of particles. With an increase in the thrust force, the reduction of particles concentration was recorded in the case of the engine powered by fuel with oil additive. There was no significant effect of oil additive on the size distribution of emitted particles.